ADVANTAGES OF COMBINATION THERAPY OF HYPERTENSION WITH CALCIUM CHANNEL BLOCKER AND ANGIOTENSIN-CONVERTING ENZYME INHIBITOR IN PATIENTS WITH IMPAIRED RENAL FUNCTION - N. A. Dzhaiani (Столичная издательская компания, 2015)
Up-to-date data on combination therapy of arterial hypertension in patients with chronic kidney disease are presented. Special attention is paid to the fixed combination of calcium antagonist lercanidipine and angiotensin-converting enzyme inhibitor enalapril.